KENANGA: WOMEN’S CULTURE (AN ANALYSIS OF NOVEL, A WORK OF FEMALE AUTHOR WITH PRESPECTIVE ELAINE SHOWALTER CULTURE MODEL) - Yessy Hermawati (Universitas Islam Sumatera Utara (UISU), 2018)
In understanding the women’s culture, historians see and distinguish various aspects of identity, roles, relationships, attitudes and pictures of women's lives formed in the culture of society in general. Female writers also express and present the women’s culture in their works. This study discusses how the women’s culture is represented in a novel written by a woman. A work that is written with attention to the cultural elements of women that presents women's lives through experience and narration. The object analyzed in this study is Oka Rusmini's novel entitled